The Influence of Perceived Justice on Recovery Satisfaction in the Airline Industry. Issue 4 (2nd October 2018) - Matikiti, Rosemary; Roberts-Lombard, Mornay; Mpinganjira, Mercy
ABSTRACT: This study examines the influence of perceived justice on customer satisfaction with service recovery and on the future behavioral intentions of customers in the airline industry. The study uses an exploratory research design that is quantitative in nature. Questionnaires were used to collect data, and structural equation modeling was used for hypothesis testing. The study revealed that the three dimensions of perceived justice, namely interactional, distributive and procedural justice, influence satisfaction with service recovery in the South African airline industry. However, only interactional and distributive justice had a positive influence on future behavioral intention.